Effect of key process variables on mechanical properties of blended vortex spun yarns. Issue 6 (3rd June 2019) - Bhatti, Muhammad Rehan Asghar; Tausif, Muhammad; Mir, Muhammad Ahsan; Umar, Muhammad; Cassidy, Tom
Abstract: A study of significant factors and their interaction during vortex yarn spinning has been carried out to achieve desired mechanical properties of the polyethylene terephthalate/cotton blended yarns which can offer process and performance advantages. The key significant factors, i.e. feed ratio, air pressure and spindle size were varied in a mixed-level factorial design. The mechanical properties (count lea strength product, tenacity and elongation at break) were studied and feed ratio was found to significantly affect the tenacity and elongation at break of spun yarns. A significant effect of these parameters was observed on the diameter and hairiness of the Muratec vortex spun yarn.